Effects of intergroup contact on explicit and implicit outgroup attitudes: A longitudinal field study with majority and minority group members. (13th July 2022) - Vezzali, Loris; Lolliot, Simon; Trifiletti, Elena; Cocco, Veronica Margherita; Rae, James Richard; Capozza, Dora; Hewstone, Miles
Abstract: A longitudinal field study tested the long‐term effects (three years) of intergroup contact on both explicit and implicit outgroup attitudes. Participants were majority (Italian) and minority (immigrant) high‐school students, who were tested at four waves from the beginning of their first year in high‐school to the end of the third school year. Results revealed, first, a longitudinal association of quantity (but not quality) of contact with lower intergroup anxiety and more positive explicit attitudes, as well as bidirectional effects over time between explicit attitudes and intergroup anxiety, on the one hand, and quantity and quality of contact, on the other. Second, reduced intergroup anxiety mediated the association between quantity of contact and improved explicit attitudes over time. Third, the product of quantity and quality of contact longitudinally predicted more positive implicit outgroup attitudes over school years. We discuss the theoretical and practical implications of findings.